Finding of Bothrocophias hyoprora in the district of Las Piedras, Madre de Dios-Perú - Rojas-Jaimes, Jesús (2021)
Ophidism is an accident with serious consequences for people linked to the ophidian accident that ends with sequelae such as organic damage and death. A snake was captured in the district of Las Piedras, Madre de Dios, Peru. The specimen was taken to the laboratory and it was taxonomically classified as Bothrocophias hyoprora. This finding was anecdotal because B. hyoprora is a poorly identified species in snake accidents and in populated areas, as it prefers areas of primary forest.